Irpex jinshaensis sp. nov. and I. subulatus comb. nov. (Irpicaceae, Polyporales), evidenced by morphological characters and phylogenetic analysis - Tian, Xue-Mei; Man, Xiao-Wu; Liu, Zhan-Bo (Phytotaxa, 2022)
A new poroid wood-inhabiting fungus in the family Irpicaceae, Irpex jinshaensis sp. nov., is described and illustrated from China based on morphological and molecular evidence. The species was collected in Yunnan Province, where it grew on the undersides of fallen angiosperm branches. I. jinshaensis is characterized by an annual growth habit, resupinate basidiocarp with white to cream pores when fresh becoming salmon to cinnamon upon drying, a monomitic hyphal system, generative hyphae thick-walled with simple septa, and occasionally covered with small crystal granules, the presence of encrusted cystidia and subglobose to globose basidiospores. The phylogenetic analysis based on ITS + nLSU rDNA sequences shows that the new species belongs to Irpex, clustering with I. hydnoides, I. hacksungii and I. lacteus with strong support. In addition, a new combination, I. subulatus, is proposed based on morphological and phylogenetic analyses. Morphological and molecular characters confirm the placement of both the new species and the combination in Irpex. A key to the species of Irpex known from China is provided.